Directionality in tree ring accumulation of tin (Sn) in three tree species - Ayse Ozturk Pulatoglu (BioResources, 2024)
The objective of this study was to determine suitable tree species to monitor and reduce Sn concentrations in the environment of Düzce province in Türkiye. A further goal was to test the hypothesis that, possibly due to air transport, the uptake of Sn in tree rings would show a significant and consistent dependency on compass direction. The timber samples were from the trunks of Tilia tomentosa (linden), Robinia pseudoacacia (black locust), Cedrus atlantica (cedar), Pseudotsuga menziesii (Douglas fir), and Fraxinus excelsior (European ash), which are commonly used in landscaping in Düzce province. Levels of Sn concentrations in annual rings were determined. Cedrus atlantica and F. excelsior were found to be suitable biomonitors that can be used to monitor changes in annual amounts of Sn contamination. Among the studied tree species, R. pseudoacacia had the highest average values and C. atlantica had the second-highest levels of Sn uptake. However, no consistent dependency on compass direction was found. It follows that rather than depending on the direction of prevailing winds, the uptake of metals to the xylem of trees must be due to direction-independent processes, such as transport via roots and xylem or absorption into leaves and subsequent transport via the phloem.
Keywords: sn; biomonitor; tin pollution; heavy metal; air quality; TP248.13-248.65; Biotechnology